Public Relations Management in Efforts to Improve School Image and Community Participation - Daman Rasman Syarif Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Schools and communities are living environment that cannot be separated. A school is a place of learning, while the community environment is a place for the implications of the education and teaching process in schools. In this study, the types of case studies are qualitative. Interviews and literary studies, field observations, and documentation were used for data collection techniques in this study. In this study, the analysis coincided with data collection on the ground. The investigator reduces data obtained in the field by analyzing the data, sorting each information by focusing on research, and drawing conclusions in each direction. Triangulation techniques (sources and methods/technics), observations and member checks are applied to check the validity of the data used in this study. From this research, it can be seen that good public relations or public relations in educational institutions are public relations that can implement the goals, visions and missions that have been set in real terms. The concept and mission are not merely a slogan but are used as the basis for carrying out these public relations duties properly. To make it happen, the vision and mission of public relations in educational institutions need to be supported and the active role of various components in the educational institution, both principals, teachers including all members of the school or educational institution. Finally, so that positive public opinion towards an educational institution can be realized, the development of the vision and mission of public relations in educational institutions based on customer satisfaction can be used as a choice for the achievement of the expected goals.